Armed Forces Redeployment Issues in the Context of Georgia-US Relations in the South Caucasus (from 1991 to 2019) - Chakhoyan, Edgar (History and Culture, 2021)
The article presents in details the issues of redeployment of the armed forces in the South Caucasus in the context of Georgia-US relations, covering the period of 1991-2019. The reasons, expectations and results of the deepening of the military direction of Georgia's military-political cooperation, its strategic alliance with the United States, are discussed in details. Attention is paid to the steps taken by the United States to withdraw the Russian military bases in Georgia, the policy of deploying American military bases instead, the resulting regional security and stability risks, and the military capabilities and modernization of military equipment in official Tbilisi.The facts and events prove that with the support of the United States, Saakashvili prepared since 2004 for the return of territories beyond the control of official Tbilisi, even if necessary, through the use of force. The impact of the military and geopolitical changes in Georgia on neighboring countries, particularly – Armenia, are presented as well. The article focuses on the study and analysis of the scope and impact of the agreements concluded between the parties. The beginning, deepening and further developments of the military-political relations between Georgia and the USA are fully emphasized. Special attention was paid to the study of the goals of Georgia-US relations in the post-Soviet period in terms of geopolitical, energy, communication, conceptual and strategic issues in the region, as well as the impact of these issues on the relations between the two countries and regional policy.
Keywords: South Caucasus; redeployment of the armed forces; military base; NATO; redistribution of military equipment; Georgia-US military-political relations; regional security; Georgian Ministry of Defense; Abkhazia; South Ossetia